tìm x và y biết 1/x^(1/2) + 1/y^(1/2)= 4 - X^(1/2) - Y^(1/2)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
bài 1 : a,ta có 3/x-1 =4/y-2=5/z-3 => x-1/3=y-2/4=z-3/5
áp dụng .... => x-1+y-2+z-3 / 3+4+5 = x+y+z-1-2-3/3+4+5 = 12/12=1
do x-1/3 = 1 => x-1 = 3 => x= 4 ( tìm y,z tương tự
Bài 1:
a) Ta có: 3/x - 1 = 4/y - 2 = 5/z - 3 => x - 1/3 = y - 2/4 = z - 3/5 áp dụng ... =>x - 1 + y - 2 + z - 3/3 + 4 + 5 = x + y + z - 1 - 2 - 3/3 + 4 + 5 = 12/12 = 1 do x - 1/3 = 1 => x - 1 = 3 => x = 4 ( tìm y, z tương tự )
- \(P=\frac{x^2+2}{1-x^3}-\frac{1}{2\left(1+\sqrt{x}\right)}-\frac{1}{2\left(1-\sqrt{x}\right)}\\ =\frac{x^2+2}{1-x^3}+\frac{-1+\sqrt{x}}{2\left(1+\sqrt{x}\right)\left(1-\sqrt{x}\right)}+\frac{-1-\sqrt{x}}{2\left(1+\sqrt{x}\right)\left(1-\sqrt{x}\right)}\\ =\frac{x^2+2}{\left(1-x\right)\left(1+x+x^2\right)}+\frac{-1}{1-x}\\ =\frac{x^2+2-\left(1+x+x^2\right)}{\left(1-x\right)\left(1+x+x^2\right)}\\ =\frac{1-x}{\left(1-x\right)\left(1+x+x^2\right)}\\ =\frac{1}{1+x+x^2}\)
b,Ta có \(\frac{x_1}{x_2}=\frac{y_1}{y_2}=\frac{y_1-x_1}{y_2-x_2}=\frac{-2}{-1}=2\)
\(\Rightarrow\hept{\begin{cases}x_1=2x_2=2.4=8\\y_1=2y_2=2.3=6\end{cases}}\)
...............
\(a,x\left(y-2\right)=8\\ \Rightarrow x;\left(y-2\right)\inƯ\left(8\right)=\left\{-8;-4;-2;-1;1;2;4;8\right\}\)
\(x\) | \(-8\) | \(-4\) | \(-2\) | \(-1\) | \(1\) | \(2\) | \(4\) | \(8\) |
\(y-2\) | \(-1\) | \(-2\) | \(-4\) | \(-8\) | \(8\) | \(4\) | \(2\) | \(1\) |
\(y\) | \(1\) | \(0\) | \(-2\) | \(-6\) | \(10\) | \(6\) | \(4\) | \(3\) |
Vậy \(\left(x;y\right)=\left(-8;1\right),\left(-4;0\right),\left(-2;-2\right),\left(-1;-6\right),\left(2;6\right),\left(4;4\right),\left(8;3\right)\)
\(b,\left(x-1\right)\left(y-2\right)=9\\ \Rightarrow\left(x-1\right),\left(y-2\right)\inƯ\left(9\right)=\left\{-9;-3;-1;1;3;9\right\}\)
\(x-1\) | \(-9\) | \(-3\) | \(-1\) | \(1\) | \(3\) | \(9\) |
\(y-2\) | \(-1\) | \(-3\) | \(-9\) | \(9\) | \(3\) | \(1\) |
\(x\) | \(-8\) | \(-2\) | \(0\) | \(2\) | \(4\) | \(10\) |
\(y\) | \(1\) | \(-1\) | \(-7\) | \(11\) | \(5\) | \(3\) |
Vậy \(\left(x;y\right)=\left(-8;1\right),\left(-2;-1\right),\left(0;-7\right),\left(2;11\right),\left(4;5\right),\left(10;3\right)\)
5: Đặt \(\dfrac{x}{5}=\dfrac{y}{3}=k\)
nên x=5k; y=3k
Ta có: \(x^2-y^2=4\)
\(\Leftrightarrow25k^2-9k^2=4\)
\(\Leftrightarrow k^2=\dfrac{1}{4}\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=\pm\dfrac{5}{4}\\y=\pm\dfrac{3}{4}\end{matrix}\right.\)